Transcription dynamics of heat-shock proteins (Hsps) and endosymbiont titres in response to thermal stress in whitefly, Bemisia tabaci (Asia-I) - Barman, Mritunjoy; Samanta, Snigdha; Ahmed, Bulbul; Dey, Soumik; Chakraborty, Swati; Deeksha, M.G.; Dutta, Subham; Samanta, Arunava; Tarafdar, Jayanta; Roy, Deepayan (Frontiers in Physiology, 2023)
The sweet potato whitefly, Bemisia tabaci (Gennadius), is one of the several species complexes of whitefly that are currently significant agricultural pests. Bemisia tabaci infests more than 600 plant species and thrives under a wide range of temperature conditions. In addition to the direct damage caused by sucking plant sap, it vectors several plant viruses. Heat-shock proteins play a pivotal role in enabling the insect to extend its geographical location, survival, and reproduction under different stress conditions. B. tabaci harbours several endosymbionts under the genera Portiera, Rickettsia, Hamiltonella, Wolbachia, Arsenophonus, Cardinium, and Fritschea that directly or indirectly affect its fitness. By accelerating cuticle biosynthesis and sclerotisation, symbiotic microbes can reduce or enhance tolerance to extreme temperatures and detoxify heavy metals. Thus, symbionts or microbial communities can expand or constrain the abiotic niche space of their host and affect its ability to adapt to changing conditions. The present study delineates the effect of thermal stress on the expression of heat-shock genes and endosymbionts in B. tabaci. Studies of the expression level of heat-shock proteins with the help of quantitative real-time polymerase chain reaction (qRT-PCR) showed that heat- and cold-shock treatment fuels the increased expression of heat-shock proteins (Hsp40 and Hsp70). However, Hsp90 was not induced by a heat- and cold-shock treatment. A significant decrease in the relative titre of secondary endosymbionts, such as Rickettsia, Arsenophonus, and Wolbachia, were recorded in B. tabaci upon heat treatment. However, the titre of the primary symbiont, C. Portiera, was relatively unaffected by both cold and heat treatments. These results are indicative of the fact that Hsp genes and endosymbionts in B. tabaci are modulated in response to thermal stress, and this might be responsible for the adaptation of whitefly under changing climatic scenario.